Encuesta sobre violencia contra las mujeres en el hogar en una localidad de Guadalupe, Zacatecas, México. Un enfoque sobre prevención social de la violencia (PAPIIT UNAM IA300118) (2022)
In the framework of a project on social prevention of violence, the results of a representative survey on domestic violence against women in a locality of Zacatecas are presented. According to a bivariate logistic regression analysis, it is concluded that younger women, who work for a salary and live in de facto unions are at greater risk of being victims of domestic violence. In contrast, women who have more freedom to make decisions and who share household chores with their partners are at lower risk. Based on these results, we outline intervention guidelines that we propose to articulate with an integral measure for the prevention of violence in the locality.